Catalytic synthesis of methacrolein via the condensation of formaldehyde and propionaldehyde with l-proline. Issue 13 (9th June 2020) - Yu, Jiayuan; Jensen, Anker Degn; Wang, Lei; Li, Chunshan; Zhang, Suojiang
Abstract : l -proline acts as an efficient catalyst for the condensation reaction to synthesize methacrolein under mild condition. Abstract : Methacrolein (MAL) is an important chemical for the manufacture of methyl methacrylate and a key monomer in many polymerization reactions. In this study, l -proline was investigated as the catalyst for the aldol condensation of formaldehyde and propionaldehyde to produce MAL. The catalytic activity of the reaction system was closely related to the competition between the main reaction synthesizing MAL and the side reaction producing 2-methyl-2-pentenal, which could be modified by adjusting the operating parameters. The influences of several operating conditions, including temperature, reaction time and water content, on the catalytic performance of the system were systematically studied via a series of single-factor experiments, and the optimized reaction conditions were obtained. The mechanistic investigation via ESI-MS indicated that the reaction pathway followed the Mannich route. Experimental and theoretical kinetic analyses of the l -proline-catalyzed aldol condensation reaction were performed, and the reaction orders of the reactants were obtained by regression. The results showed that l -proline was an efficient catalyst for the production of MAL via aldol condensation under mild conditions.